If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + 7 = 3m + -18 Reorder the terms: 7 + 2m = 3m + -18 Reorder the terms: 7 + 2m = -18 + 3m Solving 7 + 2m = -18 + 3m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3m' to each side of the equation. 7 + 2m + -3m = -18 + 3m + -3m Combine like terms: 2m + -3m = -1m 7 + -1m = -18 + 3m + -3m Combine like terms: 3m + -3m = 0 7 + -1m = -18 + 0 7 + -1m = -18 Add '-7' to each side of the equation. 7 + -7 + -1m = -18 + -7 Combine like terms: 7 + -7 = 0 0 + -1m = -18 + -7 -1m = -18 + -7 Combine like terms: -18 + -7 = -25 -1m = -25 Divide each side by '-1'. m = 25 Simplifying m = 25
| 5(2a-3)-2(a+1)= | | X^6-5x^3+6=0 | | 3(n+5)+6(4n-1)= | | ax^2+8x+32=0 | | 3t(2t-7)= | | 85=15x^2 | | 18-2(x+3)= | | (8+4)*5+10-18+7+5*(7+1*4)+6= | | 4x-4x(4x-4x)= | | 4x^2-1=8x | | 7x-97=4x-13 | | 211-4x=32x+19 | | logy=1.6 | | 2x+x+400+2x=5000 | | x(x-20)=525 | | 75-2x=2x+19 | | -16-2x=-10x | | 3(x-2)-5(3-4x)=29-2x | | p^2-20-8p=0 | | (-2.6)+7=7+(-2.6) | | 20+8p=p^2 | | 9b+36=b^2 | | 6-(-15)= | | 3x=15y | | (-3y^2)(2xy)(-x)= | | 16X^3-24x^2-12x-14=0 | | (-3y^2)(2xy)= | | 2*(2+2)/2= | | 8x^2=7x | | f^2=10f-16 | | a^2+8a-9=0 | | (c-6)(c-3)=23 |